Bimbingan Konseling dalam Upaya Menumbuhkembangkan Karakter Peserta Didik pada Era Merdeka Belajar - Mitra Sasmita (Universitas Islam Sultan Agung, 2023)
This study aims to determine the existence of counseling guidance in schools in an effort to develop the character of students at SMK Taruna Karya I Karawang in the era of independent learning. This research is a type of descriptive qualitative research in which the data are in the form of words not numbers (derived from interviews, report notes, documents and others). The population used in this study were all students of SMK Taruna Karya I Karawang. By taking a sample of 64 students from class X and 24 students from class XI. As for the steps of counseling guidance carried out at SMK Taruna Karya I Karawang in a preventive/persuasive (prevention) and curative (healing) way. Based on the results of observational data, field notes through interviews and questionnaires, it was found that preventive guidance at SMK Taruna Karya I, Karawang, reached a percentage of 80%. This shows that the results of the guidance are strong or good, considering the numbers that show often and sometimes are greater in number than never. Then with curative counseling it reached a percentage of 77.8%. It also shows that the results of the guidance are strong or good, considering the numbers that show often and sometimes are greater in number than never. Thus, the two results show that counseling guidance in an effort to develop the character of students at SMK Taruna Karya I Karawang results are good and successful